Handarbeni Batik: Batik-Making Training for Generation Z In Improving Cultural Existence - Irhamni, Muhammad Ricza; Ayuningtyas, Rosida Dwi; Islamiyah, Mahabbah (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: In today's highly diverse art and cultural landscape, it's important to have a strong sense of self-awareness. By reintroducing local culture, we can help develop a sense of belonging and appreciation for cultural heritage within communities. Preservation and development efforts are crucial for fostering the growth of culture and art, such as the Batik culture.Method: The natural dye batik training method utilizes plant-based colors found in the environment and is supported by Generation Z's entrepreneurial spirit to boost the economy and future income.Practical Applications: The purpose of this journal is to bring attention to the significance of batik and the necessity to protect it. It can be shared with government officials, policymakers, and other stakeholders who are eager to promote Indonesian culture.Conclusion: The Handarbeni Batik initiative exemplifies the symbiotic relationship between cultural preservation and economic progress. By imparting the art of batik to the next generation, this program ensures its longevity, while also empowering young individuals with the necessary skills to thrive in the contemporary job market.